The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/hbm.23846
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the role of hematocrit in between‐subject variations of MRI‐derived baseline cerebral hemodynamic parameters and functional BOLD responses

Abstract: Baseline hematocrit fraction (Hct) is a determinant for baseline cerebral blood flow (CBF) and between-subject variation of Hct thus causes variation in task-based BOLD fMRI signal changes. We first verified in healthy volunteers (n 5 12) that Hct values can be derived reliably from venous blood T 1 values by comparison with the conventional lab test. Together with CBF measured using phase-contrast MRI, this noninvasive estimation of Hct, instead of using a population-averaged Hct value, enabled more individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 74 publications
8
43
0
Order By: Relevance
“…The results suggest that it is possible that previous studies of sex differences in functional connectivity that did not control for haemoglobin may be confounded, at least in ageing (e.g., Jamadar et al, 2018). Our results are consistent with some (Xu et al;Guensch et al, 2016), but not other (Yang et al) results in healthy younger adults. Given the differences in haemoglobin concentration over the lifespan (Backman et al 2016, Cruikshank, 1970Salive et al, 1992), future studies should explore if the effect of haemoglobin on the BOLD-fMRI signal varies with age.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The results suggest that it is possible that previous studies of sex differences in functional connectivity that did not control for haemoglobin may be confounded, at least in ageing (e.g., Jamadar et al, 2018). Our results are consistent with some (Xu et al;Guensch et al, 2016), but not other (Yang et al) results in healthy younger adults. Given the differences in haemoglobin concentration over the lifespan (Backman et al 2016, Cruikshank, 1970Salive et al, 1992), future studies should explore if the effect of haemoglobin on the BOLD-fMRI signal varies with age.…”
Section: Discussionsupporting
confidence: 84%
“…The current sample is substantially larger than the previous studies of the influence of haemoglobin on BOLD-fMRI measures (Yang et al, 2015;Xu et al, 2018), with a sample size of 518 subjects. Like Xu et al (2018) our results suggest that individual differences in haemoglobin have a substantial influence on BOLD-fMRI measures of functional connectivity and functional connectivity-cognition relationships. In contrast to Yang et al (2015), we found that haemoglobin effects were widespread, spatially non-specific in men;…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is in good agreement with the report of Vernooij et al 6 It is well known that hematocrit fraction is a crucial determinant of CBF, and there exists an inverse relationship between hematocrit and CBF. 39 The normal hematocrit level ranges from 40-54% and from 36-48% for men and women, respectively. 40 The wide range of Hct among subjects may explain the larger intersubject variation of CBF.…”
Section: Discussionmentioning
confidence: 99%